Efficacy and safety of accelerated fractionated radiotherapy without elective nodal irradiation for T3N0 glottic cancer without vocal cord fixation. Issue 8 (7th February 2020) - Okumura, Masayuki; Motegi, Atsushi; Zenda, Sadamoto; Nakamura, Naoki; Hojo, Hidehiro; Nakamura, Masaki; Hirano, Yasuhiro; Kageyama, Shun‐ichiro; Arahira, Satoko; Parshuram, Raturi Vijay; Kuno, Hirofumi; Hayashi, Ryuichi; et al.
Abstract: Background: The purpose of this study was to evaluate accelerated fractionated radiotherapy (AFRT) without elective nodal irradiation (ENI) for T3N0 glottic cancer (GC) without vocal cord fixation, especially in comparison with chemoradiotherapy (CRT) and hyperfractionated radiotherapy (HFRT) both of which included ENI. Methods: The medical charts of patients with T3N0GC without cord fixation received definitive radiotherapy between June 2005 and March 2018 were reviewed. Results: A total of 74 patients were analyzed. After a median follow‐up time of 46 months (range, 12‐141), 3‐year local failure in AFRT/CRT/HFRT (n = 41/10/23) was 10%/20%/26%, 3‐year regional failure 6%/0%/9%, 3‐year progression‐free survival 71%/69%/74%, and 3‐year overall survival 77%/100%/87%. There were no significant differences among three groups in recurrence or survival. Grade 3 adverse events (AEs) were noted in 5/2/8 patients (12%/20%/35%) in AFRT/CRT/HFRT, respectively. There were no Grade 4/5 AEs. Conclusions: AFRT without ENI is an effective and feasible treatment for T3N0GC without cord fixation.